Consumer wants to entertain, to be stimulated and touched by heart: Cell phone consumption preferences of the Turkish consumers as an experiential way of consumption - Bati, U?ur; Atici, BünyamIn (Asian Research Publishing Network (ARPN), 2010)
Experiential marketing provides customers an opportunity to engage and interact with brands, products, and services in sensory ways in today's competitive markets. This research demonstrates how experiential marketing fits in with the current consumer behavior and attitudes through cell phone usage on Turkish consumers. In the research, the steps and elements of experiential marketing will be clearly defined. A questionnaire is prepared content with this research and is applied on 612 cell phone users as participants from various regions of Turkey. Sampling of the research consists of 612 participants of 18-65 age groups. The research data are analyzed in the program of SPSS 10.0 and t test, factor analysis, frequency analysis, correlation analysis and variance analysis are performed. The study indicates that the subjects on which the participants show attitude at higher level are related with the brand experience. In addition to this, it is seen that the consumers evaluated the products in the frame of the social status symbolized in their cell phone preferences in the experience of association. © 2005 - 2010 JATIT& LLS.
Keywords: Advertising; Brands; Cell phone; Experiential marketing; Hedonism